Bronchoscopic lung volume reduction with endobronchial valves for patients with heterogeneous emphysema and intact interlobar fissures (the BeLieVeR-HIFi study): a randomised controlled trial. Issue 9998 (12th September 2015) - Davey, Claire; Zoumot, Zaid; Jordan, Simon; McNulty, William H; Carr, Dennis H; Hind, Matthew D; Hansell, David M; Rubens, Michael B; Banya, Winston; Polkey, Michael I; Shah, Pallav L; Hopkinson, Nicholas S
Summary: Background: Lung volume reduction surgery improves survival in selected patients with emphysema, and has generated interest in bronchoscopic approaches that might achieve the same effect with less morbidity and mortality. Previous trials with endobronchial valves have yielded modest group benefits because when collateral ventilation is present it prevents lobar atelectasis. Methods: We did a single-centre, double-blind sham-controlled trial in patients with both heterogeneous emphysema and a target lobe with intact interlobar fissures on CT of the thorax. We enrolled stable outpatients with chronic obstructive pulmonary disease who had a forced expiratory volume in 1 s (FEV1 ) of less than 50% predicted, significant hyperinflation (total lung capacity >100% and residual volume >150%), a restricted exercise capacity (6 min walking distance <450 m), and substantial breathlessness (MRC dyspnoea score ≥3). Participants were randomised (1:1) by computer-generated sequence to receive either valves placed to achieve unilateral lobar occlusion (bronchoscopic lung volume reduction) or a bronchoscopy with sham valve placement (control). Patients and researchers were masked to treatment allocation. The study was powered to detect a 15% improvement in the primary endpoint, the FEV1 3 months after the procedure. Analysis was on an intention-to-treat basis. The trial is registered at controlled-trials.com, ISRCTN04761234. Findings: 50 patients (62% male, FEV1 [% predicted] mean 31·7% [SD 10·2]) were enrolled to receive valves (n=25) or sham valve placement (control, n=25) between March 1, 2012, and Sept 30, 2013. In the bronchoscopic lung volume reduction group, FEV1 increased by a median 8·77% (IQR 2·27–35·85) versus 2·88% (0–8·51) in the control group (Mann-Whitney p=0·0326). There were two deaths in the bronchoscopic lung volume reduction group and one control patient was unable to attend for follow-up assessment because of a prolonged pneumothorax. Interpretation: Unilateral lobar occlusion with endobronchial valves in patients with heterogeneous emphysema and intact interlobar fissures produces significant improvements in lung function. There is a risk of significant complications and further trials are needed that compare valve placement with lung volume reduction surgery. Funding: Efficacy and Mechanism Evaluation Programme, funded by the Medical Research Council (MRC) and managed by the National Institute for Health Research (NIHR) on behalf of the MRC-NIHR partnership.